1980
DOI: 10.1104/pp.65.5.797
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Light and Temperature on Monoterpene Emission Rates from Slash Pine

Abstract: High levels of ozone have been measured in rural and remote locations, far from significant anthropogenic sources of oxidant precursors. Elevated oxidant concentrations in these areas could be the result of transport into these areas and/or photooxidation of locally produced biogenic hydrocarbons. Volatile organics, including monoterpenes, have been detected in the atmosphere (I 1, 15, 18, 25), and the reports suggested that the hydrocarbons had a biogenic origin. Robinson (17) proposed that hydrocarbon conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
191
4
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(212 citation statements)
references
References 14 publications
15
191
4
2
Order By: Relevance
“…BVOC emission rates increase exponentially (up to approximately 38°C for isoprene) with. increasing leaf temperature, while isoprene emission rate also increases with increasing light intensity up to approximately 1000~tmolm-2s -1 (Guentber et al, 1993;Tingey et al, 1979Tingey et al, , 1980. Chameides et al (1988) assumed that forests in the llcounty Atlanta ozone nonattainmcnt area emit no isoprene at night, increased linearly to a rate of 2100 pg-C m-2 h-1 at noon, remained constant until 3 PM local time, and then decreased linearly to zero at 7 PM local time.…”
Section: Methodsmentioning
confidence: 99%
“…BVOC emission rates increase exponentially (up to approximately 38°C for isoprene) with. increasing leaf temperature, while isoprene emission rate also increases with increasing light intensity up to approximately 1000~tmolm-2s -1 (Guentber et al, 1993;Tingey et al, 1979Tingey et al, , 1980. Chameides et al (1988) assumed that forests in the llcounty Atlanta ozone nonattainmcnt area emit no isoprene at night, increased linearly to a rate of 2100 pg-C m-2 h-1 at noon, remained constant until 3 PM local time, and then decreased linearly to zero at 7 PM local time.…”
Section: Methodsmentioning
confidence: 99%
“…Monoterpene emissions from most plants are known to increase exponentially with temperature (Tingey et al, 1980;Juuti et al, 1990;Guenther et al, 1993). Standard emission factors (sometimes referred to as basal emission rates) are typically calculated using the Guenther et al (1993) algorithm; E meas ¼ E s exp½bðT2T s Þ that normalizes the measured emission rates at ambient temperatures to a standard temperature of 30 C. In this equation, E meas is the measured emission rate at leaf temperature T ( C), E s is the emission rate at standard temperature T s (30 C) and b ( C À1 ) is an empirical temperature coefficient ranging from 0.06 C À1 to 0.14 C À1 , with an average value of 0.09 C À1 .…”
Section: Article In Pressmentioning
confidence: 99%
“…Tingey et al, 1981;Monson and Fall, 1989;Sharkey and Loreto, 1993), nor on monoterpene emissions (e.g. Tingey et al, 1980;Loreto et al, 1996), The apparent non-dependence of VOC emissions on G s has been explained by the low concentrations of these compounds in the leaf tissue, which increase when G s decreases and which compensate for stomatal closure. Kesselmeier and Staudt (1999) also suggested that increased internal VOC concentrations could increase diffusion of monoterpene compounds through the leaf cuticular membrane.…”
Section: Pathways Of Monoterpene Emissionsmentioning
confidence: 99%